Implementasi Qanun Kabupaten Aceh Tengah Tentang Kepariwisataan Tahun 2018-2025 - Ashwad, Hajar; Zunafriesma, Nanda; Sahru Nova, Irhamna; Suknah, Suknah; Fachri, Husni (Universitas Gajah Putih, 2022)
It is very important to develop tourism destinations in Central Aceh Regency by utilizing natural resources that have the potential to become a source of regional income (PAD) and grow the economy of the local community. This study aims to analyze the Development Strategy of Natural, Cultural and Artificial Tourism Destinations in Central Aceh District. The results of this study Socialization to the community in the use of Natural Resources (SDA) in the development of natural, cultural, and artificial tourism, assistance to tourism actors in developing tourism such as the formation of Tourism Awareness Groups (POKDARWIS), creating and utilizing the selling power of local wisdom products both in terms of independently or as a tourist village group.